Philosophy and Mediation. A Manifesto - De Cesaris, Alessandro (ETHICS IN PROGRESS, 2019)
The current condition of philosophy as a discipline is quite problematic, in particular if we consider its relationship to other human sciences and to other disciplines in general. The philosophical debate appears fragmented, and philosophy itself has lost any specific role in the present scientific landscape. This situation determines a sort of “identity crisis”, whose main consequence is the coexistence of antinomical views about philosophy in the contemporary scientific and public discourse. Starting from this context, the paper aims at providing a description of philosophy as “theory of mediation”. This description does not want to be ‘original’, but rather tries to emphasize an element that is always been rooted in the very essence of philosophy, but that has also often been neglected. Philosophy has always pointed out the necessity to think the in-between of things, their relation and the passage from one to another, rather than just offering a taxonomy or a factual description of the world. In order to prove this point, the paper offers an analysis of some classical texts, in particular of some fragments by Heraclitus and of a passage taken from Hegel’s early writings. A view that rethinks philosophy as “mediology” allows a rehabilitation of philosophy as a specific discipline and as a systematic enterprise, at the same time providing a new framework for the understanding of the relationship between philosophy and other sciences.